2016
DOI: 10.1038/srep34815
|View full text |Cite
|
Sign up to set email alerts
|

Pressure induced elastic softening in framework aluminosilicate- albite (NaAlSi3O8)

Abstract: Albite (NaAlSi3O8) is an aluminosilicate mineral. Its crystal structure consists of 3-D framework of Al and Si tetrahedral units. We have used Density Functional Theory to investigate the high-pressure behavior of the crystal structure and how it affects the elasticity of albite. Our results indicate elastic softening between 6–8 GPa. This is observed in all the individual elastic stiffness components. Our analysis indicates that the softening is due to the response of the three-dimensional tetrahedral framewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 78 publications
1
21
0
Order By: Relevance
“…Mookherjee et al . [] theoretically determined values provide the only pressure derivatives available for albite (An0).…”
Section: Single‐crystal Elastic Constantsmentioning
confidence: 98%
See 4 more Smart Citations
“…Mookherjee et al . [] theoretically determined values provide the only pressure derivatives available for albite (An0).…”
Section: Single‐crystal Elastic Constantsmentioning
confidence: 98%
“…As an alternative, Mookherjee et al . [] showed that albite conversion to jadeite and quartz can lead to >1 km/s increase in velocity, from ~6.5 km/s to ~8.1 km/s. Such conversion may be occurring during the formation of the continental Moho, which would ultimately provide a very strong seismic impedance contrast between the feldspar‐rich crust and the jadeite‐rich mantle [i.e., Jagoutz and Behn , ].…”
Section: Seismic Properties Of the Continental Crust From The Mineralmentioning
confidence: 99%
See 3 more Smart Citations